ANALISIS SIFAT ADSORPSI KARBON AKTIF KAYU DAN TEMPURUNG KELAPA PADA LIMBAH CAIR BATIK DI KOTA PEKALONGAN - Nihla Nurul Laili; Mahardika Prasetya Aji; Sulhadi Sulhadi (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
Pekalongan City is a center of batik production in Central Java. Problems that arise the process of batik synthesis produce liquid waste that can damage the environment. One of the wastewater treatment of batik can be done by using activated carbon. Charcoal wood and coconut shell charcoal can be used as activated carbon. The process of carbon activation is carried out chemically with an H3PO4 acid solution for 24 hours. The resulting activated carbon is used to adsorb batik wastewater with a variation of immersion contact time. The degradation of waste color before and after active immersion was measured using a spectrometer UV-Vis. The results showed that the longer the contact time between activated carbon and batik liquid waste, the level of clarity of batik liquid waste is higher, and the more decreasing the absorbance value generated. The use of coconut shell charcoal activated carbon in batik liquid waste shows higher clarity level compared to wood activated carbon. Keywords: Wood Charcoal, Coconut Shell Charcoal, Batik Liquid Waste.